Revocable iris templates using partial sort and randomised look-up table mapping. (28th October 2022) - Sandhya, Mulagala; Vallabhadas, Dilip Kumar; Rathod, Shubham
In the ongoing years, biometric systems end up helpless against the spillage of template information. If a biometric template is stolen, it is lost permanently and cannot be restored or reissued. Here, we use iris biometric because of its high accuracy. In this paper, we develop a new cancellable biometric scheme using the indexing-first-one (IFO) hashing coupled with a technique called partial sort. The IFO hashing uses new mechanisms called the P-order Hadamard product and modulo threshold function paired with the partial sort technique which has considerably strengthened it further. We used the very sophisticated CASIA-v3 database which provides us with a wide range of iris templates for our experiments. As compared to the previous cancellable schemes, the analysis of the results of these experiments provides us with good accuracy and strong resistance to various privacy and security attacks.